Managing Maternal Anxiety in Pregnancy through Interventions and Family Support: Mengelola Kecemasan Ibu dalam Kehamilan melalui Intervensi dan Dukungan Keluarga - Arroban, Aliyah Gabriella; Azizah, Nurul (Universitas Muhammadiyah Sidoarjo, 2024)
This case study examines anxiety in pregnancy, focusing on Mrs. Y, a 35-year-old primigravida experiencing heightened anxiety due to elevated blood pressure concerns. The study aimed to alleviate her anxiety through counseling, regular prenatal monitoring, and family support. Mrs. Y's fears stemmed from family history of preeclampsia and societal misconceptions, impacting her emotional well-being. Interventions included educating the family on their supportive role, reassurance of her ability to manage pregnancy and childbirth, and fostering emotional stability. The study highlights the critical role of healthcare providers in offering comprehensive care, screening, and education to mitigate risks associated with preeclampsia, thereby enhancing maternal outcomes through emotional support and informed care. Highlights: Pregnancy anxiety impact: hypertension, tailored interventions crucial for maternal health. Counseling, prenatal monitoring vital to manage anxiety, prevent preeclampsia risks. Family support pivotal: emotional stability, informed care crucial during pregnancy. Keywords: Pregnancy Anxiety, Preeclampsia, Counseling, Family Support, Maternal Health